Morphological analysis of regenerated antennae in the isopod Porcellio scaber (Isopoda, Crustacea), with emphasis on the main sensory structures - Primož Zidar; Primož Mihelič (ZooKeys)
The second antennae, an important sensory organ of terrestrial isopods, are often attacked and amputated by predators or members of the same species. If an amputation does happen, the antenna usually regenerates after the very first or the next moult that follows. However, the new regenerated antenna is smaller than the original one. This raises the question of whether a smaller regenerated antenna is potentially also less functional as the sensory elements of the antenna undergo regeneration as well. In this study, the regeneration process of the second antenna of Porcellio scaber was followed after two consecutive amputations. The original antennae were compared with the regenerated ones under light and scanning electron microscopes in view of the dimensions of segments and the size and number of sensory elements on them. As expected, all regenerated antennae were reduced in size, however, the reduction of different antennal segments was different. The second segment of the flagellum was reduced by almost half as much as the first segment of the flagellum or the last segment of the peduncle. After the next consecutive amputation, the reduction of the regenerated antennae does not increase further. The size and shape of the apical organ and lateral seta did not change during the regeneration process, neither after the first nor after the next amputation. In contrast, the number of plural receptor elements, such as aesthetascs and tricorn sensilla, decreases in accordance with reduced segment size. Therefore, since only the number of the most common sensory structures is reduced during regeneration, the regenerated antenna probably retains its sensory functionality.